2021
DOI: 10.17843/rpmesp.2021.381.6571
|View full text |Cite
|
Sign up to set email alerts
|

Concordancia entre autotoma y colección estándar de muestras endocervicales para identificar infecciones de trasmisión sexual en un área urbano-rural del Perú

Abstract: Con el objetivo de evaluar la concordancia entre la autotoma de muestras vaginales y la toma estándar de muestras endocervicales para la identificación de Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis y Candida spp. realizadas por el personal de salud en mujeres de un área urbano-rural del Perú, se realizó un estudio prospectivo y transversal en 206 mujeres en edad fértil, identificamos algunas infecciones de transmisión sexual como Chlamydia trachomatis o Trichomonas vaginalis en 9 mujer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Eighty per cent of studies (36 of 45) detected newly diagnosed positive CT/GC infections and 42.2% of studies (19 of 45) measured test accuracy 16 17 20 22–55. Seventeen studies reported 2×2 table values 22 28 30–33 35 36 38–43 51–53. We excluded four studies where reference test was unclear/not reported 22 31–33…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighty per cent of studies (36 of 45) detected newly diagnosed positive CT/GC infections and 42.2% of studies (19 of 45) measured test accuracy 16 17 20 22–55. Seventeen studies reported 2×2 table values 22 28 30–33 35 36 38–43 51–53. We excluded four studies where reference test was unclear/not reported 22 31–33…”
Section: Resultsmentioning
confidence: 99%
“…We generated pooled diagnostic accuracy values (table 2) and SROC curves (figure 3) by sampling site and study population for CT/GC from 13 studies 28 30 32 35 38–43 51…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation